Calcium-sensing receptor (version 2020.5) in the IUPHAR/BPS Guide to Pharmacology Database - Bikle, Daniel; Bräuner-Osborne, Hans; Brown, Edward M.; Chang, Wenhan; Conigrave, Arthur; Hannan, Fadil; Leach, Katie; Riccardi, Daniela; Shoback, Dolores; Ward, Donald T.; et al. (IUPHAR/BPS Guide to Pharmacology CITE, 2020)
The calcium-sensing receptor (CaS, provisional nomenclature as recommended by NC-IUPHAR [46] and subsequently updated [76]) responds to multiple endogenous ligands, including extracellular calcium and other divalent/trivalent cations, polyamines and polycationic peptides, L-amino acids (particularly L-Trp and L-Phe), glutathione and various peptide analogues, ionic strength and extracellular pH (reviewed in [77]). While divalent/trivalent cations, polyamines and polycations are CaS receptor agonists [14, 109], L-amino acids, glutamyl peptides, ionic strength and pH are allosteric modulators of agonist function [35, 46, 60, 107, 108]. Indeed, L-amino acids have been identified as "co-agonists", with both concomitant calcium and L-amino acid binding required for full receptor activation [147, 53]. The sensitivity of the CaS receptor to primary agonists is increased by elevated extracellular pH [17] or decreased extracellular ionic strength [108]. This receptor bears no sequence or structural relation to the plant calcium receptor, also called CaS.